2021
DOI: 10.3168/jds.2020-19868
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the cholesterol esterase- and lipase-inhibiting potential of bioactive peptides from camel whey hydrolysates: Identification, characterization, and molecular interaction

Abstract: Novel antihypercholesterolemic bioactive peptides (BAP) from peptic camel whey protein hydrolysates (CWPH) were generated at different time, temperature, and enzyme concentration (%). Hydrolysates showed higher pancreatic lipase-(PL; except 3 CWPH) and cholesterol esterase (CE)-inhibiting potential, as depicted by lower half-maximal inhibitory concentration values (IC 50 values) compared with nonhydrolyzed camel whey proteins (CWP). Peptide sequencing and in silico data depicted that most BAP from CWPH could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…For example, FGAPR, FPFVPAPT, and FPFPPTLGY could bind up to 13, 12, and 11 bound residues on the active sites of PL (i. e. Phe78, Phe216, His152, Ser153, and His264), respectively. Similar binding hot spots for lipase inhibiting peptides from camel whey protein hydrolysates have been reported by Baba et al (2021) . From the APHs (AB-4), peptide MPFLPR, FPFVGP, FPFPPTLGY, FGAPR and FPFVPAPT were predicted to bind to the highest number of hotspots on the active site of PL.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…For example, FGAPR, FPFVPAPT, and FPFPPTLGY could bind up to 13, 12, and 11 bound residues on the active sites of PL (i. e. Phe78, Phe216, His152, Ser153, and His264), respectively. Similar binding hot spots for lipase inhibiting peptides from camel whey protein hydrolysates have been reported by Baba et al (2021) . From the APHs (AB-4), peptide MPFLPR, FPFVGP, FPFPPTLGY, FGAPR and FPFVPAPT were predicted to bind to the highest number of hotspots on the active site of PL.…”
Section: Resultssupporting
confidence: 81%
“…From this study, peptides that showed the ability to bind to important amino acids of lipase were of hydrophobic amino acid supremacy i.e. leucine and proline Ngoh et al, 2017 , Baba et al, 2021 observed similar results in pinto beans and camel whey protein hydrolysates, respectively. They reported that in most of the lipase inhibiting peptides, proline and leucine are identified as the interacting residues.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Recently, production of modified whey-polyphenol conjugates with enhanced techno-functional as well as bioactive properties is generating high research interest and has been identified as the hotspot in the field of food science [13] . Moreover, recent research on whey proteins from camel milk is gaining considerable importance in today’s world due to its therapeutic properties [3] , [6] , [7] . Camel whey has been reported for their high techno-functional potential that warrants its use in food industry [32] , [33] , [68] .…”
Section: Introductionmentioning
confidence: 99%